Penguatan Karakter Islami Peserta Didik Melalui Implementasi Pendekatan Pembelajaran Kontekstual pada Mata Pelajaran PAI di SMK Bina Karya 1 Karanganyar - Ramadhan, Gilang; Rinawati, Atim (IAINU Kebumen, 2024)
Research objectives: (1) to describe the mechanism for implementing contextual learning in Islamic Religious Education subjects at SMK Bina Karya 1 Karanganyar. (2) to knowing the Islamic character of the students at SMK Bina Karya 1 Karanganyar after implementing contextual learning in Islamic Religious Education subjects. Based on the research results, it is concluded that: 1) The mechanism for implementing the contextual learning approach is carried out in three stages, namely the learning planning stage, learning implementation, and learning evaluation. At the planning stage the teacher prepares the teaching module and all the requirements for the learning process. The implementation of learning is carried out as formulated in the teacher's teaching module, containing the opening of the lesson, core learning activities and closing of the lesson. At the learning evaluation stage the teacher gives assignments to assess student learning outcomes regarding the material that has been discussed. The process of implementing the contextual learning approach in PAI subjects at SMK Bina Karya 1 Karanganyar class XI TP 1-4 as a whole went smoothly according to the learning plans that had been prepared by the teacher. 2) Implementation of the contextual learning approach in PAI subjects class XI TP 1-4 SMK Bina Karya 1 Karanganyar, researchers concluded it was successful. This is evident from the research results which show changes in students' character from before and after implementing the contextual learning approach. Reflecting on the four mandatory characters for the apostles, in Siddiq's character, students are initially less honest in doing their assignments and become more honest in doing their assignments. In the Amanah character, initially the students were less polite and became more polite. In the Fathonah character, students initially lack discipline but become well disciplined, and in the Tabligh character, initially irresponsible students become more responsible when given teacher assignments after implementing a contextual learning approach